The Influence of AI Chatbots on the Purchase Intention of Sustainable Products - Bozdog, Luminita-Stefania; Naghi, Remus Ionut; Preda, Gheorghe; Prada, Sorin Ioan (Transformations In Business & Economics, 2025)
This study investigates the influence of AI chatbots on consumers' purchase intentions of sustainable products. The primary objective is to assess how the use of AI chatbots affects environmental awareness, perceived value, and attitudes towards sustainable products, and how these factors, in turn, impact purchase intentions. Data were collected through an online questionnaire with 562 respondents and analysed using structural equation modelling (SEM). The results show that AI chatbots significantly enhance environmental awareness, perceived value, and positive attitudes towards sustainable products. Furthermore, environmental awareness and perceived value positively impact both attitudes and purchase intentions. This study highlights the potential of AI chatbots as a powerful tool in promoting sustainable consumption, emphasizing their role in shaping eco-friendly purchasing behaviours. Future research should explore the moderating effects of variables such as trust and technological literacy.
Keywords: AI Chatbots; Sustainable Products; Environmental Awareness; Purchase Intention; Perceived Value